Screening of Bacillus thuringiensis strains effective against mosquitoes - Monnerat, Rose Gomes; Dias, Daniel Gerhein Souza; Silva, Silvania Ferreira da; Martins, Erica Soares; Berry, Colin; Falcão, Rosana; Gomes, Ana Cristina Menezes Mendes; Praça, Lilian Botelho; Soares, Carlos Marcelo Silveira (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate 210 Bacillus thuringiensis strains against Aedes aegypti and Culex quinquefasciatus larvae to select the most effective. These strains were isolated from different regions of Brazil and are stored in a Bacillus spp. collection at Embrapa Recursos Genéticos e Biotecnologia, Brasília, Brazil. The selected strains were characterized by morphological (microscopy), biochemical (SDS-PAGE 10%) and molecular (PCR) methods. Six B. thuringiensis strains were identified as mosquito-toxic after the selective bioassays. None of the strains produced the expected PCR products for detection of cry4, cry11 and cyt1A genes. These results indicate that the activity of mosquitocidal Brazilian strains are not related with Cry4, Cry11 or Cyt proteins, so they could be used as an alternative bioinsecticide against mosquitoes.